Clinical Profile of Acute Poisoning in Children at a Teaching Hospital in Lalitpur - Dhakal, Ajaya Kumar; Shrestha, D; Shakya, A; Shah, SC; Shakya, H (Journal of Nepal Paediatric Society, 2014)
Introduction: Acute poisonings are one of the common cause of emergency visits and hospital admissions and is potentially preventable cause of childhood mortality and morbidity. The objectives of this study were to identify the common type of poisoning in children, to determine types of poisoning according to age and to find out the common age group in which the incidence of poisoning was high. Materials and Methods: It was a descriptive observational study done in a teaching hospital in Lalitpur, Nepal in patients aged 1 month to 18 years who visited the emergency department and were admitted to hospital with history of alleged poisoning from 2009 July to 2014 January. Results: Fifty patients were included. Drugs, kerosene and organophosphorus were most common cause of poisoning. Drugs and kerosene below 10 years of age and organophosphorus and drugs above 10 years of age were common types of poisoning. Maximum numbers (50%) of children with poisoning cases were below five year of age. Mean duration of hospital stay was 2.1days and mean age of poisoning was 7.8 years with a male(54%) predominance. Majority of poisoning occurred at home (84%) and 68% of patients were symptomatic at presentation to hospital with 84% of patients presenting to hospital within six hours. Conclusion: This study showed that drugs, kerosene and organophosphorus were most common forms of poisoning. Young children were most vulnerable for acute poisoning. DOI: http://dx.doi.org/10.3126/jnps.v34i2.10139 J Nepal Paediatr Soc 2014;34(2):100-103